MODEL FOR FORECASTING WIND DIRECTION AT AN ALTITUDE OF 120 METERS IN KOH PHAYAM, MUEANG RANONG, RANONG - Riansut, Warangkhana (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The aim of this research is to construct seven methods of forecasting wind direction at an altitude of 120 meters in Koh Phayam, Mueang Ranong, Ranong, namely, Box-Jenkins method, Holt’s exponential smoothing method, Brown’s exponential smoothing method, damped trend exponential smoothing method, simple seasonal exponential smoothing method, Winters’ additive exponential smoothing method, and Winters’ multiplicative exponential smoothing method. Time series of hourly wind direction were gathered from research center in energy and environment, Thaksin university during 1 July to 1 October 2015 of 2,209 observations. The criteria of the lowest mean absolute percentage error and root mean squared error were used for comparing the suitability of the forecasting model. The study indicated that Brown’s exponential smoothing method was the most appropriate (MAPE = 8.694, RMSE = 24.682).